2017
DOI: 10.1111/cge.13030
|View full text |Cite
|
Sign up to set email alerts
|

Galactose‐1‐phosphate uridyltransferase deficiency: A literature review of the putative mechanisms of short and long‐term complications and allelic variants

Abstract: Galactosemia type 1 is an autosomal recessive disorder of galactose metabolism, determined by a deficiency in the enzyme galactose-1-phosphate uridyltransferase (GALT). GALT deficiency is classified as severe or variant depending on biochemical phenotype, genotype and potential to develop acute and long-term complications. Neonatal symptoms usually resolve after galactose-restricted diet; however, some patients, despite the diet, can develop long-term complications, in particular when the GALT enzyme activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 113 publications
(281 reference statements)
0
20
0
8
Order By: Relevance
“…The impact of abnormal glycosylation on the physiological function of different glycoproteins and glycolipids has been considered a contributing factor to galactosemia complications (Liu et al 2012;C o s se ta l .2014a, b). Recent in vitro and in vivo studies have also demonstrated the increase in oxidative stress and downregulation of PI3K/Akt pathway in response to the impaired GALT function (Jumbo-Lucioni et al 2013;Balakrishnan et al 2016), although the understanding of the complex interplay between these different mechanisms is still limited (Viggiano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of abnormal glycosylation on the physiological function of different glycoproteins and glycolipids has been considered a contributing factor to galactosemia complications (Liu et al 2012;C o s se ta l .2014a, b). Recent in vitro and in vivo studies have also demonstrated the increase in oxidative stress and downregulation of PI3K/Akt pathway in response to the impaired GALT function (Jumbo-Lucioni et al 2013;Balakrishnan et al 2016), although the understanding of the complex interplay between these different mechanisms is still limited (Viggiano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Life-long galactose restricted diet is the only treatment currently available for this condition. Although this treatment is life-saving in the neonate, long-term complications including cognitive impairment, neurological and speech abnormalities, and fertility problems in female patients, persist in treated adult patients despite early diagnosis and initiation of treatment [ 1 8 ]. Ovarian damage and subfertility with primary ovarian insufficiency (POI) is a major complication for females causing a very significant disease burden.…”
Section: Introductionmentioning
confidence: 99%
“…2 Symptoms such as failure to thrive, poor feeding, vomiting, diarrhea, jaundice, hepatomegaly, present themselves in newborns with galactosemia. 3 Untreated galactosemia can lead to liver disease, renal tubular dysfunction, Escherichia coli sepsis, and neonatal death. 4 Newborn screening for galactosemia largely eliminates neonatal death through early identification and prompt treatment with a galactose-free diet.…”
Section: Introductionmentioning
confidence: 99%